P05.39 Skull-base chordoma treated with proton and carbon ion radiotherapy: C.N.A.O. clinical experience. (19th September 2018) - Iannalfi, A; D'Ippolito, E; Vitolo, V; Vischioni, B; Fiore, M; Bonora, M; Ronchi, S; Caivano, D; Barcellini, A; Mirandola, A; Molinelli, S; Russo, S; et al.
Abstract: Background: Skull-base chordomas are rare and malignant tumors that originate from remnants of the chorda dorsalis (notochord). Adjuvant radiotherapy (RT) is an important predictor of improved progression-free survival and it is recommended after surgery. Exclusive RT represents the treatment of choice for unresectable chordomas. Particle radiotherapy provides dosimetric advantages and higher biological effective dose especially for radioresistant tumors. The aim of the study was to evaluate local control (LC) and toxicity profile of patients (pts) with skull-base chordoma treated with exclusive or adjuvant particle therapy (proton therapy -PT- and carbon ion therapy -CIRT-) Material and Methods: Between September 2011 and December 2017, a total of 134 pts (79 men and 55 women) with a median age of 57 years (range 14–86) with histologically proven skull-base chordoma were treated with particle therapy at National Center of Oncological Hadrontherapy -CNAO. One-hundred and two (76%) pts had previous surgery and complete macroscopic resection was achieved only in 15 pts (20%). Sixty-one pts were treated with PT and 73 with CIRT. The particle choice (proton or carbon ion) was made on personalized basis. Median prescribed total dose was 70, 4 Gy RBE (range 35, 2-70, 4 Gy RBE) in 8–22 fractions (median 16 fractions) of 3-4, 4 Gy RBE (median 4, 4 Gy RBE) for CIRT, and 74 Gy RBE (range 70–74 Gy RBE) in 27–37 fractions (median 37 fractions) of 2 Gy RBE for PT. Clinical outcome (LC, 3 year local relapse free- LRFS and overall -survival -OS-) and toxicity profile were evaluated. Results: The median follow-up was 32 months (range, 2–64 months). LC was 83%. In pts that underwent complete macroscopic surgery followed by PT, LC was 100%, in pts with uncomplete resection/only biopsy and PT/CIRT, LC was 79%. The 3-year LRFS and OS were 80% and 90% respectively. In field recurrence occurred in 13% (18 pts). In 16 out of 18 cases of recurrences the tumor was in close contiguity to the brainstem. Out of field recurrence was found in 5 pts: 2 cases occurred within surgical way, attributable to surgical seeding, One case of histologically confirmed cervical lymph-node relapse, 2 cases of newly appeared nodules of recurrence. Six pts (4%) developed distant metastasis after a mean interval of 12 months. The toxicity profile was favorable. Only 2 pts developed acute radiation induced high grade toxicity: with oral mucositis (grade 3). High grade (G3-G4) late toxicity occurred in 4% of pts: 1 case of complete visual loss (G4) expected because of optic nerve in field, 1 case of soft tissue necrosis, 2 cases of cranial nerve neuropathy and 2 cases of pituitary dysfunction. Conclusion: Particle therapy is the most innovative and conformal RT for treatment of skull base chordomas. It allows to deliver higher (biologically effective) dose levels and to obtain high tumor control rates, minimizing radiation-related side effects.